Associations between Attention-Deficit Hyperactivity Disorder (ADHD) Treatment and Patient Nutritional Status and Height - Mariana F. Granato; Alexandre A. Ferraro; Denise M. Lellis; Erasmo B. Casella (Behavioural Neurology)
Attention-deficit hyperactivity disorder (ADHD) has been found to co-occur frequently with obesity, although the reasons for this association are unknown. The aim of this study was to compare the nutritional profile of a Brazilian cohort of ADHD patients with that of the general population and to analyze the association between ADHD drug treatment (with methylphenidate), nutritional status, and height of these individuals. In the first phase of the study, we designed the nutritional and height profile of 93 ADHD patients (5.1 to 13.8 years old) and compared it to a control group. In the second phase, we analyzed the association of the use of methylphenidate with nutritional status and height. The results showed that the prevalence of overweight/obesity was statistically higher in the cohort of ADHD patients compared to controls (40.9% vs. 34.7%; P<0.05). After treating ADHD patients with methylphenidate, a statistically significant decrease in the BMI z-score was observed (0.695 vs. 0.305; P<0.01). On the other hand, no significant impact on height was detected after treatment (0.189 vs. 0.248; P=0.298). In conclusion, the results suggest that the use of methylphenidate in patients who have ADHD and obesity is relevant not only for controlling ADHD symptoms but also for improving the nutritional status of these individuals. Moreover, the treatment did not affect the patients’ height.